Some sensitive issues in the use and development of the anthropological theory of the didactic Quelques questions sensibles dans l’utilisation et le développement de la théorie anthropologique du didactique - Chevallard, Yves (Educação Matemática Pesquisa Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2020)
Abstract This presentation repeats the opening lecture that the author gave on January 23, 2018 in Autrans (France) during the 6th International Congress on the ATD. Something of the oral form has been deliberately preserved in the text proposed here to the reader. As the title indicates, the aim was to draw attention to certain difficulties observed in the reception and use of the ATD. It is these difficulties that the structure of the text seeks to highlight and help overcome. After having underlined the question of the vocabulary specific to the ATD, we successively examine its theory of cognition, which is the basis of the ATD, then the cardinal notion of the possibly didactic, before moving on to the theory of praxeologies, which has undoubtedly received the greatest diffusion so far, and to progress by deepening the dialectic of persons and institutional positions, before specifying the concept of inquiry, which is at the heart of the current and future developments of the ATD. Keyword: Anthropological Theory of Didactics, Theory of cognition, Possibly didactic Résumé Cet exposé reprend la conférence inaugurale que l’auteur a prononcée le 23 janvier 2018 à Autrans (France) dans le cadre du 6e congrès international sur la TAD. Quelque chose de la forme orale a été volontairement conservé dans le texte proposé ici au lecteur. Comme l’indique le titre, il s’agissait d’attirer l’attention sur certaines difficultés observées dans la réception et l’usage de la TAD. Ce sont ces difficultés que la division du texte s’efforce de mettre en évidence et d’aider à dépasser. Après avoir souligné la question du vocabulaire propre à la TAD, on examine successivement la théorie de la cognition, qui constitue la base de la théorie, puis la notion cardinale du possiblement didactique, avant d’aborder la théorie des praxéologies, qui a reçu sans doute la plus grande diffusion jusqu’ici, et de progresser en approfondissant la dialectique des personnes et des positions institutionnelles, avant de préciser le concept d’enquête, qui est au cœur des développements en cours et à venir de la TAD. Mots-clés : Théorie Anthropologique du Didactique, Théorie de la cognition, Possiblement didactique.